Toll-Like Receptor 7/8 Ligand, S28463, Suppresses Ascaris suum-induced Allergic Asthma in Nonhuman Primates - Camateros, Pierre; Kanagaratham, Cynthia; Najdekr, Lukáš; Holub, Dušan; Vrbkova, Jana; Coté, Lucie; Fournier, Jocelyn; Gourdon, Jim; Creery, David; Olivenstein, Ron; Kopriva, Frantisek; Adam, Tomáš; et al. (American journal of respiratory cell and molecular biology, 2018)
S28463 (S28), a ligand for Toll-like receptor 7/8, has been shown to have antiinflammatory properties in rodent models of allergic asthma. The principle goal of this study was to assess whether these antiinflammatory effects can also be observed in a nonhuman primate (NHP) model of allergic asthma. NHPs were sensitized then challenged with natural allergen, Ascaris suum extract. The animals were treated with S28 orally before each allergen challenge. The protective effect of S28 in NHPs was assessed by measuring various asthma-related phenotypes. We also characterized the metabolomic and proteomic signatures of the lung environment and plasma to identify markers associated with the disease and treatment. Our data demonstrate that clinically relevant parameters, such as wheal and flare response, blood IgE levels, recruitment of white blood cells to the bronchoalveolar space, and lung responsiveness, are decreased in the S28-treated allergic NHPs compared with nontreated allergic NHPs. Furthermore, we also identified markers that can distinguish allergic from nonallergic or allergic and drug-treated NHPs, such as metabolites, phosphocreatine and glutathione, in the plasma and BAL fluid, respectively; and inflammatory cytokines, IL-5 and IL-13, in the bronchoalveolar lavage fluid. Our preclinical study demonstrates that S28 has potential as a treatment for allergic asthma in primate species closely related to humans. Combined with our previous findings, we demonstrate that S28 is effective in different models of asthma and in different species, and has the antiinflammatory properties clinically relevant for the treatment of allergic asthma.
Keywords: interleukin-13; Interleukin-5; proteiny červů; Toll-Like Receptor 8; inflammation; Allergens; bronchiální astma; Ascaris suum; toll-like receptor 8; Helminth Proteins; proteomics; alergeny; Asthma; zvířata; experimental model; Interleukin-13; metabolomics; treatment; Toll-Like Receptor 7; interleukin-5; toll-like receptor 7; Macaca fascicularis; Animals